Pengaruh Kepuasan Kerja, Motivasi dan Disiplin Kerja Terhadap Produktivitas Karyawan Pada PT. Kusuma Mulia Plasindo Infitex Klaten - Utomo, Sabekti Jati; , Dr. Triyono, S.E., M.Si (2016)
The purpose of this study was to determine and analyze the Influence of job satisfaction, motivation and the Discipline of the Productivity of employees working on PT. Kusuma Mulia Plasindo Infitex Klaten, then the purpose of this study was to reveal the influence job satisfaction, motivation and the Discipline of the Productivity of employees working either individually or together -same. The population in this study were all employees at PT. Kusuma Mulia Plasindo Infitex. Where the method of determining the sample using random sampling or simple random sampling. So that as many as 437 employees of the population earned 60 employees in the sample. The data in this study using primary data obtained directly from a sample of 60 respondents. Testing the hypothesis in this study using multiple linear regression techniques, t test and F test with SPSS 16. Where hypothesis testing using a significance level of 0.05. Based on the test results are statistically can be seen clearly that the partial all independent variables affect the dependent variable. The third influence given the independent variables are positive means higher job satisfaction, motivation and discipline of work, the resulting higher the productivity of employees that produced. These results are consistent with the hypothesis put forward. This is indicated by the results of multiple linear regression is Y = 4.375 + 0.223 + 0.259 X1 + 0.362 X2 + X3 + e. Where does this mean that if there is no job satisfaction, motivation and discipline of work, the productivity of employees amounted to 4.375.